A Guide to the Florida 4-H Council - Stacey E. Ellison; Tracy Tesdall; J. A. Rutledge; Joy C. Jordan; Wendi Armstrong (EDIS)
The 4-H Program utilizes many tools or methods to provide educational experiences for youth. The 4-H Council (or other relevant named groups) at county, district, and state levels is one of these tools. A Council is an elected representative group of 4-H members who meet, discuss, plan, and assist in carrying out 4-H programs and activities in the interest of the total membership. The Council provides a link between local clubs or groups and County 4-H Programs, between County Programs and District 4-H Programs, and between District Programs and State 4-H Programs. This revised 11-page guide was written by Stacey E. Ellison, Tracy Tesdall, J. A. Rutledge, Joy C. Jordan, and Wendi Armstrong, and published by the UF Department of 4-H Youth Development, October 2014.